2021
DOI: 10.1038/s41398-021-01387-7
|View full text |Cite
|
Sign up to set email alerts
|

Parkin regulates drug-taking behavior in rat model of methamphetamine use disorder

Abstract: There is no FDA-approved medication for methamphetamine (METH) use disorder. New therapeutic approaches are needed, especially for people who use METH heavily and are at high risk for overdose. This study used genetically engineered rats to evaluate PARKIN as a potential target for METH use disorder. PARKIN knockout, PARKIN-overexpressing, and wild-type young adult male Long Evans rats were trained to self-administer high doses of METH using an extended-access METH self-administration paradigm. Reinforcing/rew… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…METH is an extremely dangerous substance, widely regarded as the most poisonous and addictive, 26 because it stimulates 10 times the normal amount of dopamine production and causes considerable harm. 27 METH induces cardiac injury by multifactorial pathways, according to a growing number of studies published in the previous few years.…”
Section: Discussionmentioning
confidence: 99%
“…METH is an extremely dangerous substance, widely regarded as the most poisonous and addictive, 26 because it stimulates 10 times the normal amount of dopamine production and causes considerable harm. 27 METH induces cardiac injury by multifactorial pathways, according to a growing number of studies published in the previous few years.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al showed that studying the neuronal substrates underlying "resilience" or vulnerability to METH use disorder can be facilitated by using rats with excess or deficit PARKIN. Additionally, PARKIN may be a novel therapeutic target for the treatment of METH use disorder [154]. After METH withdrawal, protein ubiquitination and E3 ubiquitin ligases are increased in the central amygdala.…”
Section: Histones Ubiquitinationmentioning
confidence: 99%
“…Parkin increases the ubiquitination of substrate proteins to enhance their degradation. Parkin activity is associated with METH addiction in rats (Sharma et al, 2021). Protein ubiquitination and E3 ubiquitin ligases are increased in the central amygdala (CeA) after METH withdrawal.…”
Section: Ubiquitination and Methamphetamine Addictionmentioning
confidence: 99%